2011
DOI: 10.1111/j.1465-3362.2011.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Baseline assessment of community knowledge and attitudes toward drug use and harm reduction in Kabul, Afghanistan

Abstract: Community acknowledgement of problem drug use and support for addiction treatment are present in Kabul, Afghanistan. However, knowledge gaps concerning drug laws and harm reduction should be addressed in efforts to introduce culturally appropriate harm reduction programming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…A study by Osis et al (1993) found a higher use of services by the inhabitants of the interior cities (medical appointments) which may be associated with differences in the access to care [20]. Therefore, for our study, residing in interior cities could result in less competition for the performance of the outpatient procedure.…”
Section: Discussionmentioning
confidence: 84%
“…A study by Osis et al (1993) found a higher use of services by the inhabitants of the interior cities (medical appointments) which may be associated with differences in the access to care [20]. Therefore, for our study, residing in interior cities could result in less competition for the performance of the outpatient procedure.…”
Section: Discussionmentioning
confidence: 84%
“…Statements with less than 20% of participants differing from the majority were considered to have consensus. Consistent with the baseline analysis, the 80% mark was selected to highlight the most controversial positions (13,15,16). For statements demonstrating > 10% change in consensus, sociodemographic and experiential (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The eligibility criteria and recruitment of participants was described in the report of the baseline assessment in 2007 (13). A cross-sectional convenience sample of community representatives was recruited.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations